An African glass frog: A new Hyperolius species (Anura: Hyperoliidae) from Nyungwe National Park, southern Rwanda - Dehling, J. Maximilian (Zootaxa, 2012)
A new species of Hyperolius is described from Nyungwe National Park in southern Rwanda. The new species differs fromits congeners by a unique combination of morphological characters, including a light green dorsum and a transparentventral skin resembling glass frogs of the Neotropical family Centrolenidae, blue-coloured bones, reduced toe webbing,relatively wide head, acuminate snout, small to medium size (SUL of adult males 18.8–23.2 mm), and the presence ofnuptial pads. The advertisement call differs from all calls of other species of the genus that have been analyzed.Comparison of the mitochondrial 16S rRNA gene showed a relatively close relationship to H. castaneus, H.cystocandicans, H. discodactylus, H. frontalis, and H. lateralis. The 16S sequence of the new species differs by at least 4.5% in the uncorrected p-distance from all available sequences of other species of the genus.Ubwoko bushya bwa Hyperolius buboneka muri parike nasiynali ya Nyungwe mu majyepfo yu Rwanda. Ubu bwokobushya butandukaniye na bugenzi bwabwo gusa kurusobe rw’miterere yabwo, harimo dorsum ifite ibara ry’cyatsi cyeru-rutse n’ruhu rubonerana rwo kunda, amagufwa afite ibara ry’bururu, n’tunodufatanijwe n’gahu, umutwe wenda kubamunini, umunwa uurungushuye, umubyimba uri hagati ya 18,8 mm kugera kuri 23,3 mm ku ngabo nkuru, ikagira n’mag-aragamba ku ruhu. Kuzitangaza kwazo byagiye bitandukana n’matangazo yabaye kubundi bwoko bwazo. Ugereanijen’miterere yazo idahinduka (mitochondrial 16S rRNA gene) niyizindi usanga bifitanye isano ya bugufi na H. castaneus,H.cystocandicans, H.discodactylus, H.frontalis na H. lateralis. Urukurikirane rwa 16S y’bu bwoko bushya rutandukanye kuri 4,5% ugereranije n’nkurikirana zabaye z’bundi bwoko busa n’bu.